Nanoencapsulated chrysin protects against cadmium-induced renal tissue injury through modulation of oxidative stress, inflammatory responses, mitochondrial dysfunction, and apoptotic pathways - Ekramy M. Elmorsy; Ayat B. Al-Ghafari; Huda A. Al Doghaither; Muhammad Jan; Syed Sajid Hussain Shah; Asmara Syed; Eman M. Fawzy; Gehad E. Elshopakey (Tissue and Cell, 2026)

Nanoliposomal myricetin attenuates diabetic testicular tissue injury and cellular dysfunction via coordinated modulation of PI3K/AKT/mTOR/SREBP-1c, Nrf2/HO-1, NF-κB, and caspase signaling pathways - Ekramy M. Elmorsy; Ayat B. Al-Ghafari; Huda A. Al Doghaither; Muhammad Jan; Syed Sajid Hussain Shah; Asmara Syed; Basma H. Marghani; Gehad E. Elshopakey (Tissue and Cell, 2026)

Engineering metal organic framework 808 and MXene Interfaces for sustainable oxygen evolution electrocatalysis in alkaline media - Shumaila Bibi; Syed Shoaib Ahmad Shah; Muhammad Irfan; Faiza Jan Iftikhar; Mohamed H. Helal; Muhammad Zahid Qureshi; Shu-Juan Bao; Aziz ur Rehman (Fuel, 2026)

Graphitization of banana peel – synergistic effect of Ca and other elements of the biomass on carbon structure transformation - Muhammad Jamshaid Shabbir; Barbara Liszka; Magdalena Szubka; Mirosława Pawlyta; Maciej Zubko; Jan Ilavsky; Karolina Jurkiewicz (Biomass and Bioenergy, 2026)

Rice husk-derived nanosilica alleviates aluminum accumulation and toxicity in Brassica napus by regulating cellular metabolism and antioxidant defense - Raheel Munir; Nazia Jan; Bahar Ali; Rana Muhammad Amir Gulzar; Muhammad Haseeb Javaid; Iqbal Hussain; Yinbo Gan (Environmental Research, 2026)

Lactiplantibacillus plantarum AS21 Reduces Colitis in Mice by Modulating Inflammation, Gut Barrier Function, and Microbiota in an Intervention Dose and Time-dependent Manner - Ali Sher Bacha; Mengyan Chen; Zitong Ding; Mengya Jia; Hu Chen; Ikram Khan; Muhammad Ishaq; Azmat Ullah Jan; Ashiq Khan; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Daturaolone from Datura metel L. Inhibits acetylcholinesterase and monoamine oxidase B - Bilal Khan; Marryum; Abdur Rauf; Ayesha Tahir; Umer Rashid; Hira Naeem; Muhammad Saeed Jan; Muhammad Shafique; Saima Naz; Alessandra Gianoncelli; Giovanni Ribaudo (Natural Product Research, 2026)

Harnessing biostimulants to alleviate potentially toxic element stress in vegetable crops - Amna Jamil; Waqas Liaqat; Asia Maqbool; Pramod Sargar; Muhammad Anwar-Ul-Haq; Shraddha Samindre; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed; Muhammad Tanveer Altaf (Planta, 2026)

Pharmacokinetic evaluation and in vivo anti-inflammatory potential of cyanoacetate derivatives of succinimide - Aini Pervaiz; Muhammad Saeed Jan; Ali Khan; Bushra Ansari; Imad Ahmad; Wadood Ali Shah; Syed Muhammad Mukarram Shah; Abdur Rauf; Abdullah S. M. Aljohani; Waleed Al Abdulmonem; Marcello Iriti (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
The purpose of the study is to evalute the in vivo anti -inflammatory activity of newly synthesized cyanoacetate derivatives of succinimides (C-23, C-31, and C-44) and to elucidate their possible mechanisms of action through key inflammatory mediator pathways. Anti-inflammatory activity was assessed using carrageenan-induced paw oedema and arachidonic acid-induced ear oedema models in vivo. Mechanistic involvement was investigated through histamine-, prostaglandin-, leukotriene-, and bradykinin-induced paw oedema assays. In silico ADME studies were performed to predict pharmacokinetic properties and metabolic interactions. All tested compounds exhibited significant anti-inflammatory activity, with C-44 showing the highest potency. Mechanistic studies indicated that the anti-inflammatory effects were predominantly mediated via inhibition of prostaglandin and leukotriene pathways. ADME predictions suggested high gastrointestinal absorption, favourable oral bioavailability, and minimal interaction with major metabolic enzymes. The synthesized cyanoacetate derivatives, particularly C-44, demonstrate promising anti-inflammatory potential with favourable pharmacokinetic profiles, supporting their candidacy for further development as effective anti-inflammatory agents.

Probiotics unveiled: bridging general health benefits to the era of precision medicine - Mati Ullah; Muhammad Rizwan; Muhammad Ihtesham Waheed; Muhammad Shoaib Alam; Sami Ullah Jan; Ali Raza; Muhammad Faisal Shahid; Vivian Andoh; Yong Chen (World Journal of Microbiology and Biotechnology, 2026)

Elicitors in Plant Defense: Exploring Their Role in Biotic and Abiotic Stress Resistance - Muhammad Tanveer Altaf; Waqas Liaqat; Muhammad Aneeq Ur Rahman; Chidera Anuforo; Asia Maqbool; Amjad Ali; Muhammad Faheem Jan; Muhammad aasim; Heba I. Mohamed; Faheem Shehzad Baloch (Journal of Plant Growth Regulation, 2026)

Erratum to: Bifidobacterium animalis subsp. lactis and Enterococcus hirae Enhance Immunity by Modulating Gut Microbiota and Metabolic Pathways in Immunosuppressed Mice - Azmat Ullah Jan; Hu Chen; Muhammad Ishaq; Mengya Jia; Ali Sher Bacha; Qiang Li; Mengyan Chen; Zitong Ding; Xusheng Guo (Probiotics and Antimicrobial Proteins, 2026)

Inter-device interaction effects on turbine performance and blade loads in axially aligned tidal turbine arrays - Mujahid Badshah; Saeed Badshah; Sajjad Ahmad; Imtiaz Alam Shah; Zia Ur Rehman; Muhammad Amjad; Sakhi Jan (Ocean Engineering, 2026)

Managing Basin Vulnerability Under Uncertainty: A Confidence-Based Framework for Small-Sample Water Resources Decisions - Fatima Zahra Kherazi; Dongying Sun; Charafa El Rhadiouini; Jan Muhammad Sohu; Sonia Najam Shaikh; Sanam Soomro (Water Resources Management, 2026)

Neural network-driven exploration of wave phenomena in ocean and fluid environments - Usman Younas; Fengping Yao; Jan Muhammad (Ocean Engineering, 2026)

Investigating the higher-dimensional dynamical perspective of the Boiti–Leon–Manna–Pempinelli equation for modeling complex wave interactions in fluid systems - Jianglong Shen; Jan Muhammad; Usman Younas (Ocean Engineering, 2026)

Influence of inter-device spacing on performance and blade loads in staggered arrays of tidal current turbines - Mujahid Badshah; Saeed Badshah; Zia Ur Rehman; Sajjad Ahmad; Muhammad Amjad; Sakhi Jan; Imtiaz Alam Shah (Ocean Engineering, 2026)

Unraveling the endocrine disruption potential of microplastics in testosterone regulation - Muhammad Babar Khawar; Ali Afzal; Kashifa Jalil; Tayyba Jan; Zaira Ahmad; Amna Rehman; Hanan Afzal; Sadia Ahmad; Afzal Nimra; Muhammad Ahsan Ashraf (Journal of Environmental Sciences, 2026)

Microplastics as Trojan horses: Vectors of pathogens, pollutants, and antimicrobial resistance genes - Ghazala Saeed; Ali Afzal; Afzal Nimra; Zaira Ahmad; Amna Rehman; Kaleem Maqsood; Tayyba Jan; Muhammad Ishfaq Ahmad; Naveed Karim; Byong-Hun Jeon; Ghulam Mustafa; Fakhar Zaman; et al. (Environmental Research, 2026)

Nonlinear wave dynamics of soliton neuron model: a high-fidelity computational investigation - Usman Younas; Jan Muhammad (Modeling Earth Systems and Environment, 2026)

Comprehensive in-vitro study of anticholinesterase, anti-inflammatory, and antidiabetic properties of congress grass (Parthenium hysterophorus) methanolic extract - Abdur Rauf; Muhammad Ibrahim; Yahya S. Al-Awthan; Omar S. Bahattab; Hassan A. Hemeg; Anees Ahmed Khalil; Ahood Khalid; Samiah Shahid; Hina Gull; Muhammad Saeed Jan; Dorota Formanowicz; Marcello Iriti (Plant Biosystems, 2026)

Computational exploration of Aegle marmelos coumarins: DFT, molecular docking, and dynamics studies for anti-hypertensive activity - Jan Alam; Muhammad Ali Versiani; Nadeem Ahmed; Syed Intasar Husain Taqvi; Syed Tahir Ali; Zaheer Ul-Haq (Natural Product Research, 2026)

Investigating the wave dynamics and interaction structures: Exploring the Benney-Roskes/Zakharov-Rubenchik model in the oceanic atmosphere - Jianglong Shen; Jan Muhammad; Usman Younas (Ocean Engineering, 2026)

Fe-MIL-101/Ti3C2Tx heterostructures via In-Situ solvothermal strategy for efficient oxygen evolution reaction - Shumaila Bibi; Muhmmad Irfan; Faiza Jan Iftikhar; Inas A. Ahmed; Muhammad Zahid Qureshi; Ahsan Sharif; Shu-Juan Bao; Aziz ur Rehman (Fuel, 2026)

The Ability of Probiotic Strain Escherichia coli O83:K24:H31 to Modulate Gut Homeostasis and Immune Function After Antibiotic-Induced Dysbiosis - Eliška Miková; Eliška Krčmářová; Viktor Černý; Lydie Sklenářová; Pavla Avramová; Eliška Protivová; Barbora Slunéčková; Muhammad Akhtar; Jan Věcek; Jan Procházka; Agnieszka Kubik-Zahorodna; Petra Petrásková; et al. (Probiotics and Antimicrobial Proteins, 2026)
A healthy microbiome and a homeostatic interaction between the microbiome and the host immune system are essential for proper nutrition and overall health. Excessive use of antibiotics (ATB) can disrupt the healthy gut microenvironment, leading to dysbiosis, a condition linked to a wide range of disorders and diseases. Alterations in the composition and function of the microbiota have been associated with a broad spectrum of pathological conditions. In this work, we investigated the effect of ATB administration on microbiota composition and immune modulation, with a particular focus on neutrophil dynamics. We evaluated the capacity of the probiotic strain Escherichia coli O83:K24:H31 (EcO83) to mitigate ATB-induced dysbiosis and restore immune function. As expected, ATB treatment reduced microbiota diversity, which was partially restored by EcO83 supplementation. Furthermore, ATB administration affected the expression of tight junction proteins in the small intestine, an effect reversed by EcO83 treatment. Notably, our data indicate that ATB-induced dysbiosis accelerates neutrophil aging and reduces the release of neutrophils from the bone marrow. EcO83 supplementation counteracts these effects by promoting the influx of newly generated neutrophils into circulation. Overall, our findings confirm that ATB treatment disrupts gut microbiota homeostasis, adversely affecting immune function, including neutrophil turnover. However, probiotic supplementation with EcO83 can at least partially restore microbiome composition and immune homeostasis, highlighting its potential therapeutic application in mitigating ATB-induced dysbiosis.

A review of ice accretion, detection, and mitigation methods for the gondola infrastructure application - Hamza Asif; Muhammad S. Virk; Jan-Arne Pettersen; Pourya Pourhejazy (Cold Regions Science and Technology, 2026)

Unlocking the Functional Dynamics of ERF013 in Arabidopsis thaliana: A Key Player in Plant Growth Regulation - Rahmatullah Jan; Lubna; Saleem Asif; Zakirullah Khan; Muhammad Farooq; Eman R. Elsharkawy; Sajjad Asaf; Kyung-Min Kim (Journal of Plant Growth Regulation, 2026)

Integrative regulatory networks modulating arbuscular mycorrhizal symbiosis - Yaseen Khan; Sulaiman Shah; Muhammad Faheem Jan; Mohammed Bouskout (Rhizosphere, 2026)

Mapping Urban Water Stress and Human-Water Conflicts: a Climate–Ecosystem Framework for Sustainable Water Management - Fatima Zahra Kherazi; Dongying Sun; Jan Muhammad Sohu; Charafa El Rhadiouini; Sonia Najam Shaikh (Water Resources Management, 2026)

Neural network assisted symbolic analysis and simulation of nonlinear dynamical equation - Jan Muhammad; Fengping Yao; Usman Younas (Modeling Earth Systems and Environment, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Beyond limitations: Integrating advanced analytical techniques for a new era of soil organic matter characterization - Adnan MUSTAFA; Qudsia SAEED; Lasisi H. TOBILOBA; Yakov KUZYAKOV; Muhammad NAVEED; Mohammad T.K. NEZHAD; Muhammed M. IBRAHIM; Jan FROUZ; Martin BRTNICKY; Jiri KUCERIK; Xiankai LU (Pedosphere, 2026)

Novel efficacy of pregnane and flavonoid glycosides from Desmidorchis flava in in vivo nociceptive and inflammatory paradigms and their target prediction by cheminformatics approach - Ajmal Khan; Hamdy Kashtoh; Najeeb Ur Rehman; Muhammad Shahid; Irfan Ullah; Asaad Khalid; Afnan Jan; Sobia Ahsan Halim; Kwang-Hyun Baek; Ahmed Al-Harrasi (Natural Product Research, 2025)

Alleviating stocking density stress in juvenile rainbow trout (Oncorhynchus mykiss) through dietary nano-selenium: Effects on growth, antioxidant activity, and immune response - Mashooq Ali; Aqsa Akram; Farid Ahmad Jan; Aziz Ahmad; Ashiq Hussain; Fahim Ullah Khan; Muhammad Arshad (Journal of Trace Elements in Medicine and Biology, 2025)

The art of bringing extinction to a freeze - History and future of species conservation - Thomas Hildebrandt; Susanne Holtze; Muhammad Agil; Pierfrancesco Biasetti; Julia Bohner; Miguel Casares; Loles Carbonell; Silvia Colleoni; Hayden Cuthill; Barbara De Mori; Sebastian Diecke; Cesare Galli; et al. (Cryobiology, 2025)

Consortium of Endophytic Bacillus australimaris CK11 and Staphylococcus epidermidis CK9 from Commiphora gileadensis Mediates Tomato Resilience to Combined Salinity, Heat, and Drought Stresses - Syed Saad Jan; Nasir Ali Khan; Sajjad Asaf; Raheem Shahzad; Lubna; Muhammad Imran; Saqib Bilal; In-Jung Lee; Ahmed Al-Harrasi (Journal of Plant Growth Regulation, 2025)

Growth, Yield, and Oil Quality of Sesame (Sesamum indicum L.) Cultivars Under Varying Row Spacings and Biofertilizer Application - Saddam Hussain; Abdul Qayyum; Amanullah Jan; Muhammad Ilyas; Izaz Ahmad; Uzair Ahmed; Emanuele Radicetti; Adil Mihoub; Aftab Jamal; Yaser Hassan Dewir (International Journal of Plant Production, 2025)

From green HR to environmental excellence: the synergistic impact of green HRM and big data analytics from manufacturing industry - Sonia Najam Shaikh; Li Zhen; Jan Muhammad Sohu; Fatima Zahra Kherazi; Sanam Soomro; Suman Najam Shaikh (Clean Technologies and Environmental Policy, 2025)

From global challenges to specific solutions: climate change impacts on agriculture with a focus on sorghum through bibliometric analysis - Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Faheem Jan; Haseeb Ahmad; Ehtisham Hassan Khan; Celaleddin Barutçular; Gönül Cömertpay; Faheem Shehzad Baloch; Heba I. Mohamed (Cereal Research Communications, 2025)

Dietary levan as a feed additive: Effects on growth performance, meat quality, immune response, and gut health in broiler chickens - Damian Konkol; Marta Kuźmińska-Bajor; Jan P. Madej; Ewa Popiela; Magdalena Lis; Maciej Kuczkowski; Marianna Szczypka; Kamil Sierżant; Muhammad Umair Ashgar; Katarzyna Leicht; Małgorzata Korzeniowska; Cassandra Ceccopieri; et al. (Animal Feed Science and Technology, 2025)

Enhancing underwater acoustic orthogonal frequency division multiplexing based channel estimation: a robust convolution-recurrent neural network framework with dynamic signal decomposition - Mansoor Jan; Muhammad Aman; Syed Agha Hassnain Mohsan; Samih M. Mostafa; Faten Khalid Karim (Frontiers in Marine Science, 2025)
Introduction Underwater acoustic (UWA) communication systems confront significant challenges due to the unique, dynamic, and unpredictable nature of acoustic channels, which are impacted by low signal-to-noise ratio (SNR), severe multipath propagation, latency, Doppler spread, and a shortage of real-world data. Orthogonal frequency division multiplexing (OFDM) is essential for establishing resilient and reliable data transmission in these challenging environments, but accurate channel estimation remains a critical barrier to unlocking its full potential—especially given the limitations of conventional estimation methods in adapting to UWA channel dynamics. Methods This work introduces a Convolution-Recurrent Neural Network (CRNet) estimator integrated with dynamic signal decomposition (DSD) techniques (e.g., Local Mean Decomposition, LMD; Empirical Mode Decomposition, EMD) to estimate UWA-OFDM channel characteristics and mitigate noise-induced distortions in received signals. The CRNet architecture combines convolutional layers (to capture spatial features) and recurrent layers (to model temporal dependencies), enabling it to learn complex UWA channel dynamics. The model is trained using paired data: received pilot symbols, transmitted pilots, and accurate channel impulse responses (CIR). Post-training, CRNet operates using only the received signal as input, eliminating the need for supplementary channel characteristics like SNR. To ensure real-world relevance, training and testing datasets are generated via the Bellhop ray-tracing model, which simulates diverse UWA environments (shallow coastal and continental shelf). Results Numerical findings demonstrate that the proposed CRNet model consistently outperforms benchmark methods—including least squares (LS), minimal mean square error (MMSE), and backpropagation neural network (BPNN)—across key metrics: bit error rate (BER), amplitude error, and phase error. CRNet exhibits superior performance with QPSK modulation compared to QAM, and maintains robustness even with a small number of pilot symbols. Performance evaluations on both training and unseen datasets confirm its resilience and flexibility in demanding UWA environments, validating its ability to generalize to dynamic channel conditions beyond training scenarios. Discussion The CRNet estimator addresses critical limitations of conventional UWA-OFDM channel estimation methods: its dual focus on spatial and temporal features (via convolutional-recurrent layers) overcomes the static linear constraints of LS/MMSE, while DSD-driven noise mitigation enhances input signal quality for more accurate estimation. By eliminating reliance on post-training supplementary channel data (e.g., SNR), CRNet simplifies real-world deployment. Its superior BER performance and adaptability to diverse UWA environments (shallow coastal, continental shelf) position it as a robust solution for improving the reliability and efficiency of UWA communication systems.

Distinct climate sensitivity and resilience mechanisms of pedunculate oak (Quercus robur L.) across a temperature gradient - Marko Stojanović; Soham Basu; Sergei Mikhailov; Paweł Hawryło; Jarosław Socha; Stjepan Mikac; Domagoj Trlin; Andrea Seim; Manfred Hotter; Katharina Lapin; Tamás Márton Németh; Norbert Móricz; et al. (Forest Ecology and Management, 2025)

Next-generation strategies for nitrogen-efficient maize production for a greener tomorrow - Muhammad Faheem Jan; Waqas Liaqat; Muhammad Tanveer Altaf; Muhammad Dawood Ahmadzai; Asia Maqbool; Faheem Shehzad Baloch; Ming Li (Field Crops Research, 2025)

Analytical solutions of the eighth-order (3+1)-dimensional Kac–Wakimoto equation modeling waves in ocean engineering - Jan Muhammad; Ghulam Hussain Tipu; Usman Younas (Modeling Earth Systems and Environment, 2025)

Dose-dependent efficacy and safety of Filgotinib in moderate to severe Crohn’s disease: a grade-assessed systematic review and meta-analysis of randomized controlled trials - Mohamed S. Elgendy; Ahmed Raza; Mohamed Rifai; Wajeeh Ur Rehman; Ahmed Emara; Muhammad Haris Khan; Ayiz Jan; Muhammad Younas; Anum Nawaz; Ubaid Khan (European Journal of Clinical Pharmacology, 2025)

Enhancing agricultural sustainability through the combined use of bio-slurry and chemical fertilizers: Insights from field trials in pea and radish - Abdul Baseer Khan; Matiullah Khan; Taqi Raza; Malik Badshah; Muhammad Ishtiaq Ali; Faisal Jan; Asif Jamal; Zaixing Huang (Bioresource Technology Reports, 2025)

The green supply chain conundrum: exploring the interplay of practices, performance, and technology in shaping SME sustainability in developing country - Ikramuddin Junejo; Jan Muhammad Sohu; Aiza Aziz Qureshi; Saba Shaikh; Faisal Ejaz; Tahir Saeed Jagirani; Md Billal Hossain (Environment, Development and Sustainability, 2025)

The miRNA-based liquid biopsies for environmental health risk assessment: Insights into arsenic-induced hepatotoxicity and systemic health impacts - Muhammad Yasir Abdur Rehman; Marcel van Herwijnen; Riffat Naseem Malik; Jacco Jan Briedé; Julian Krauskopf (Science of The Total Environment, 2025)

Approaches for the amelioration of adverse effects of drought stress on soybean plants: from physiological responses to agronomical, molecular, and cutting-edge technologies - Muhammad Faheem Jan; Muhammad Tanveer Altaf; Waqas Liaqat; Changzhuang Liu; Heba I. Mohamed; Ming Li (Plant and Soil, 2025)

Wave propagation and multistability analysis to the modified fractional KDV-KP equation in diversity of fields - Jan Muhammad; Usman Younas (Modeling Earth Systems and Environment, 2025)

Asteraceae in Pakistan and Kashmir with special emphasis on distribution pattern and endemism - Muhammad Qaiser; Anjum Perveen; Jan Alam; Haidar Ali; Roohi Abid (Genetic Resources and Crop Evolution, 2025)

The use of phytobiotics in the form of complexed organometallic phytoncides and micronized herbs in the nutrition of Ross 308 broiler chickens: Effects on growth performance, meat quality, and immune response - Marcin Gumowski; Cassandra Ceccopieri; Jan P. Madej; Katarzyna Leicht; Małgorzata Korzeniowska; Anna Lipińska; Kamil Sierżant; Damian Konkol; Henryk Różański; Muhammad Umair Asghar; Mariusz Korczyński (Animal Feed Science and Technology, 2025)

The Indonesian Throughflow regulated Australian summer monsoon across the Mid-Brunhes Event - Muhammad Sarim; Jian Xu; Xin Cheng; Peng Zhang; Junwen Wang; Maqsood Ur Rahman; Tayyab Jan; Hammad Ahmad (Quaternary Science Reviews, 2025)

Chlorophyll fluorescence: a smart tool for maize improvement - Muhammad Faheem Jan; Ming Li; Waqas Liaqat; Muhammad Tanveer Altaf; Changzhuang Liu; Haseeb Ahmad; Ehtisham Hassan Khan; Zain Ali; Celaleddin Barutçular; Heba I. Mohamed (Cereal Research Communications, 2025)

In-vitro, in-vivo and computational experiments for the antidiabetic potential of bioactive compound from Notholirion thomsonianum - Abdulaziz Hassan Alhasaniah; Abdul Sadiq; Ahmed Abdullah Al Awadh; Yahya I. Asiri; Meriem Rezigue; Rehman Zafar; Sajjad Ahmad; Muhammad Saeed Jan; Mater H. Mahnashi (Natural Product Research, 2025)

Tabrizicola caldifontis sp. nov., Isolated from Hot Spring Sediment Sample - Neeli Habib; Inam Ullah Khan; Muhammad Saqib; Mohammad Saeid Hejazi; Vahideh Tarhriz; Sohail Ahmad Jan; Cynthia Meza; Aparna Banerjee; Manik Prabhu Narsing Rao; Wen-Jun Li (Current Microbiology, 2025)

Enhancing irrigation scheduling by application efficiency estimations and soil moisture simulations - Jan Lukas Wenzel; Julia Pöhlitz; Muhammad Usman; Thomas Piernicke; Christopher Conrad (European Journal of Agronomy, 2025)

Energy conservation research trajectories: A systematic analysis of methods, technologies, and knowledge gaps - Bushra Jan; Muhammad Asif (Energy and Buildings, 2025)

Spatiotemporal pattern of climatic water balance over Balochistan, Pakistan for the period 1961–2016 - Muhammad Qasim; Kamal Ahmed; Aman Jan; Najeebullah Khan; Atif Muhammad Ali (Theoretical and Applied Climatology, 2025)

Comet Assay and Micronucleus Test in Circulating Erythrocytes of Ctenopharyngodon idella Exposed to Nickel Oxide Nanoparticles - Jamshid Khan; Nazish Shah; Farmanullah Dawar; Iqra Irfan; Adil Jan; Muhammad Ismail Khan; Muhammad Khisroon (Biological Trace Element Research, 2025)

Bio-catalytic activity of novel poly(ethylene glycol) methacrylate hybridized silver nanomaterials - Natasha Anwar; Mohib Shah; Saad Haroon Anwar; Muhammad Ishaq Ali Shah; Amir Zada; Hammad Ahmad Jan; Abeer Hashem; Graciela Dolores Avila-Quezada; Elsayed Fathi Abd-Allah (South African Journal of Botany, 2025)

Predictive modeling of emulsion stability and drop characteristics using machine learning: A study on surfactant influence and time dynamics - Hasnain Ahmad Saddiqi; Asmat Ullah; Zainab Javed; Qazi Muhammad Ali; Muhammad Bilal Jan; Iftikhar Ahmad; Farooq Ahmad (Food and Bioproducts Processing, 2025)

Nanosilica and salicylic acid synergistically regulate cadmium toxicity in rice - Sajid Muhammad; Zaid Ulhassan; Raheel Munir; Muhammad Umair Yasin; Faisal Islam; Kangni Zhang; Weiqi Chen; Mehmood Jan; Muhammad Afzal; Ali Muhammad; Fakhir Hannan; Weijun Zhou (Environmental Pollution, 2025)

Energy use behavior research: A scientometric evaluation and critical synthesis - Bushra Jan; Muhammad Asif; Ibrahim Yahaya Wuni (Energy and Buildings, 2024)

Strategies and bibliometric analysis of legumes biofortification to address malnutrition - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Celaleddin Barutçular; Muhammad Azhar Nadeem; Heba I. Mohamed (Planta, 2024)

Dynamic interplay of silica-coated iron oxide nanocomposite on soil-plant system to mitigate Cd toxicity in rice - Faisal Islam; Muhammad Saad Shoaib Khan; Sulaiman Ahmed; Aziz Ul Ikram; Fakhir Hannan; Mehmood Jan; Muhammad Sajid; Ali Ahmed Zaky Shoaib; Shan Liu; Jian Chen (Journal of Cleaner Production, 2024)

Effect of alfalfa-grass mixed culture and inoculation with Azotobacter and Rhizobium on soil biological properties and nutrient transformation activities - Jiri Holatko; Martin Brtnicky; Antonin Kintl; Tivadar Baltazar; Ondrej Malicek; Adnan Mustafa; Jiri Skladanka; Jiri Kucerik; Saud Alamri; Jan Lochman; Pavel Horky; Daniela Knotova; et al. (European Journal of Soil Biology, 2024)

A Bibliometric Analysis of Genome-wide Association Study (GWAS) and Sorghum (Sorghum bicolor L) Based on Web of Science Using VOS Viewer - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Muhammad Faheem Jan; Faheem Shehzad Baloch; Heba I. Mohamed (Journal of Soil Science and Plant Nutrition, 2024)

A Critical Review: Breeding Objectives, Genomic Resources, and Marker-Assisted Methods in Sorghum (Sorghum bicolor L.) - Muhammad Tanveer Altaf; Waqas Liaqat; Amna Jamil; Heba I. Mohamed; Muhammad Fahad; Muhammad Faheem Jan; Faheem Shehzad Baloch (Journal of Soil Science and Plant Nutrition, 2024)

Zinc solubilizing bacteria synergize the effect of zinc sulfate on growth, yield and grain zinc content of rice (Oryza sativa) - Muhammad Shakeel; Fauzia Yusuf Hafeez; Imran Riaz Malik; Abdur Rauf; Farooq Jan; Ikramullah Khan; Iram Ijaz; Mohamed Farouk Elsadek; Muhammad Ajmal Ali; Kamran Rashid; Muhammad Muzammal; Muhammad Munir; et al. (Cereal Research Communications, 2024)
Zinc solubilizing bacteria inhabiting root endosphere possesses great potential to enhance plant yield by solubilizing the nutrients. The potential of Zn solubilizing bacteria Bacillus sp. SH-10 and Bacillus cereus SH-17 to improve yield and grain zinc content of rice was investigated under different regimes of individual and co-inoculation in the presence and absence of chemical fertilizer zinc sulfate (ZnSO 4 ). The strains were applied to the rice varieties basmati 385 and super basmati under field conditions for two consecutive years. A significantly improved growth of rice plants, such as plant height (102–118 cm), number of tillers per plant (8.5–11.5), chlorophyll content (29.5–35.1), zinc requiring enzymes, i.e., superoxide dismutase (396–570 per gram fresh weight (g −1 FW)), carbonic anhydrase activity (CA) (10–15.06 U g −1 FW) and grain yield (3.0–3.8 tons ha −1 ), was observed in the plants inoculated with Bacillus sp. in the presence of chemical fertilizer (ZnSO 4 ). Consortium of zinc solubilizing bacteria also caused higher grain Zn content (25.0–30.5 mg kg −1 ) of the rice varieties basmati 385 and super basmati as compared to that of un-inoculated plants. Hence, it can be concluded that Zn solubilizing bacteria has immense potential to be used as agricultural crop inoculants as they synergize the effect of chemical Zn, increase yield and improve the nutritional value of crops.

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Energizing rural Pakistan through optimization of stand alone hybrid systems with techno-economic, multi-criteria decision and sensitivity analysis - Muhammad Zubair; Irshad Ullah; Abdulaziz Alanazi; Mohana Alanazi; Imad Hassan; Shayan Tariq Jan (Environment, Development and Sustainability, 2024)

Cenchrus ciliaris L. ameliorates cigarette-smoke induced acute lung injury by reducing inflammation and oxidative stress - Muhammad Irfan Aslam; Saad Touqeer; QurratUlAin Jamil; Muhammad Irfan Masood; Adeel Sarfraz; Shafaat Yar Khan; Muhammad Saeed Jan; Sulaiman Mohammed Abdullah Alnasser; Ashfaq Ahmad; Fatima Aslam; Shahid Muhammad Iqbal (South African Journal of Botany, 2024)

Enhancing wheat performance through phosphorus and zinc management strategies under varied irrigation regimes - Abdul Latif Jan; Amanullah; Adil Mihoub; Muhammad Fawad; Muhammad Farhan Saeed; Imad Khan; Emanuele Radicetti; Aftab Jamal (Environment, Development and Sustainability, 2024)

Depositional and diagenetic studies of clastic reservoirs zone in the Cretaceous Lower Goru Formation, Sindh Monocline, South Pakistan - Jawad Ahmed Jan; Mumtaz Muhammad Shah; Hamad ur Rahim; Shahid Iqbal; Samina Jahandad; Muhammad Jamil; Rayan Khalil; Yawar Amin (Journal of Earth System Science, 2024)

Comparative resistance of wheat genotypes to aphid infestation under varied sowing dates - Muhammad Nawaz; Irfanullah Khan; Farman Ullah Dawar; Ibni Amin Khalil; Zahid Hussain; Jan Saad; Syed Majid Rasheed; Khan Rahamdad (Ecological Genetics and Genomics, 2024)

Depositional and diagenetic studies of the middle Jurassic Samana Suk Formation in the Trans Indus Ranges and western extension of Hill Ranges, Pakistan: an integrated sedimentological and geochemical approach - Muhammad Shahzeb; Mumtaz Muhammad Shah; Hamad ur Rahim; Jawad Ahmed Jan; Imran Ahmad; Rayan Khalil; Kamran Shehzad (Carbonates and Evaporites, 2024)

Sublethal impacts of Buprofezin and Pyriproxyfen on cotton mealybug Phenacoccus solenopsis through transgenerational hormesis - Sabir Hussain; Khalid Ali Khan; Muhammad Rafiq Shahid; Tooba Ather; Lal Khan; Amna Bibi; Sadia Kanwal; Nadia Hussain Ahmad; Ali Jan Bugti (Phytoparasitica, 2024)

Integrated Continuous Process Design for Crystallisation, Spherical Agglomeration, and Filtration of Lovastatin - Cameron J. Brown; John McGinty; Muhammad T. Islam; Nazer Rajoub; Omid Arjmandi-Tash; Sara Ottoboni; Muhid Shahid; Stephanie J. Urwin; Ye Seol Lee; Magdalene W. S. Chong; Foteini Papathanasiou; Aruna S. Prakash; et al. (Journal of Pharmaceutical Innovation, 2024)
Purpose This work seeks to improve the particle processability of needle-like lovastatin crystals and develop a small-footprint continuous MicroFactory for its production. Methods General conditions for optimal spherical agglomeration of lovastatin crystals and subsequent product isolation are developed, first as batch processes, and then transferred to continuous MicroFactory operation. Results Methyl isobutyl ketone is a suitable bridging liquid for the spherical agglomeration of lovastatin. Practical challenges including coupling unit operations and solvent systems; mismatched flow rates and inconsistent suspension solid loading were resolved. The successful continuous production of lovastatin spherical agglomerates (D 50 = 336 µm) was achieved. Spherical agglomeration increased the density of the bulk lovastatin powder and improved product flowability from poor to good, whilst maintaining lovastatin tablet performance. Conclusion A continuous, integrated MicroFactory for the crystallisation, spherical agglomeration, and filtration of lovastatin is presented with improved product particle processability. Up to 16,800 doses of lovastatin (60 mg) can be produced per day using a footprint of 23 m 2 .

Isolation, invitro, invivo anti-inflammatory, analgesic and antioxidant potential of Habenaria plantegania Lindl - Osama M. Alshehri; Madeeha Shabnam; Saeed Ahmed Asiri; Mater H. Mahnashi; Abdul Sadiq; Muhammad Saeed Jan (Inflammopharmacology, 2024)

Isolation and characterization of Rhizobium from non-leguminous potato plants: New frontiers in Rhizobium research - Tahir Naqqash; Kauser Abdullah Malik; Asma Imran; Sohail Hameed; Muhammad Shahid; Muhammad Kashif Hanif; Afshan Majeed; Muhammad Arshad; Jan Dirk van Elsas (Biology and Fertility of Soils, 2024)

Sorghum: a Star Crop to Combat Abiotic Stresses, Food Insecurity, and Hunger Under a Changing Climate: a Review - Waqas Liaqat; Muhammad Tanveer Altaf; Celaleddin Barutçular; Heba I. Mohamed; Haseeb Ahmad; Muhammad Faheem Jan; Ehtisham Hassan Khan (Journal of Soil Science and Plant Nutrition, 2024)

Meta-review on Perforation Model of Subarachnoid Hemorrhage in Mice: Filament Material as a Possible Moderator of Mortality - Serdar Alpdogan; Timo Sander; Rui Zhang; Dilaware Khan; Xuanchen Li; Huakang Zhou; Ke Li; Ann-Christin Nickel; Baolong Zheng; Anastasiya Skryabin; Simon Schieferdecker; Björn B. Hofmann; et al. (Translational Stroke Research, 2024)
Robust preclinical models are inevitable for researchers to unravel pathomechanisms of subarachnoidal hemorrhage (SAH). For the mouse perforation model of SAH, the goal of this meta-review was the determination of variances in mortality, SAH severity grade, and vasospasm, and their experimental moderators, as many researchers are facing with incomparable results. We searched on the databases PubMed , Embase , and Web of Science for articles describing in vivo experiments using the SAH perforation mouse model and measuring mortality, SAH grade, and/or vasospasm. After screening, 42 articles (total of 1964 mice) were included into systematic review and meta-analysis. Certain model characteristics were insufficiently reported, e.g., perforation location (not reported in six articles), filament (material ( n = 15) and tip texture ( n = 25)), mouse age ( n = 14), and weight ( n = 10). Used injective anesthetics and location of perforation showed large variation. In a random-effects meta-analysis, the overall animal mortality following SAH was 21.3% [95% CI: 17.5%, 25.7%] and increased with longer observational periods. Filament material significantly correlated with animal mortality ( p = 0.024) after exclusion of hyperacute studies (time after SAH induction < 24 h). Reported mean SAH grade was 10.7 [9.6, 11.7] on the scale of Sugawara (J Neurosci Methods 167:327–34, 2008). Furthermore, mean diameter of large cerebral arteries after SAH was reduced by 27.6% compared to sham-operated non-SAH mice. Uniforming standards of experimental procedures and their reporting are indispensable to increase overall comparability.

2-Hydroxybenzohydrazide as a novel potential candidate against nociception, inflammation, and pyrexia: in vitro, in vivo, and computational approaches - Gowhar Ali; Nazar Ul Islam; Muhammad Qaim; Rahim Ullah; Muhammad Saeed Jan; Khadija Shabbiri; Muhammad Shafique; Muhammad Ayaz (Inflammopharmacology, 2024)

Melatonin alleviated cadmium accumulation and toxicity by modulating phytohormonal balance and antioxidant metabolism in rice - Raheel Munir; Muhammad Umair Yasin; Muhammad Afzal; Mehmood Jan; Sajid Muhammad; Nazia Jan; Chen Nana; Faisal Munir; Hamza Iqbal; Faiza Tawab; Yinbo Gan (Chemosphere, 2024)

Therapeutic Role of Hemp (Cannabis sativa) Against Copper-Induced Toxicity in Labeo rohita and Cirrhinus mrigala - Azam Jan Afridi; Amina Zuberi; Ali Muhammad Yousafzai; Muhammad Kamran (Biological Trace Element Research, 2024)

Surveillance of pesticide residues in tomato and eggplant and assessment of acute and chronic health risks to the consumers in Pakistan - Aasma Bibi; Farida Anjum; Syed Roohul Hussain; Abdul Ahad; Azeem Ud Deen; Muhammad Suleman; Bilal Jan (Environmental Science and Pollution Research, 2023)

Unlocking green innovation and environmental performance: the mediated moderation of green absorptive capacity and green innovation climate - Sadaf Akhtar; Cai Li; Jan Muhammad Sohu; Yasir Rasool; Muhammad Iatzaz Ul Hassan; Muhammad Bilal (Environmental Science and Pollution Research, 2023)

Emissions from modern engines induce distinct effects in human olfactory mucosa cells, depending on fuel and aftertreatment - Laura Mussalo; Simone Avesani; Muhammad Ali Shahbaz; Táňa Závodná; Liudmila Saveleva; Anssi Järvinen; Riikka Lampinen; Irina Belaya; Zdeněk Krejčík; Mariia Ivanova; Henri Hakkarainen; Juho Kalapudas; et al. (Science of The Total Environment, 2023)

Future prospects of biomass waste as renewable source of energy in Pakistan: A mini review - Waqas Ahmad; Jan Nisar; Farooq Anwar; Faisal Muhammad (Bioresource Technology Reports, 2023)

Improved bio-oil yield from thermo-catalytic pyrolysis of Citrus limetta waste over pumice: Determination of kinetic parameters using Kissinger method - Faisal Muhammad; Jan Nisar; Ghulam Ali; Farooq Anwar; Syed Tasleem Hussain; Sher Wali Khan (Bioresource Technology Reports, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Effect of different concentrations of pyridoxine on physiological indices of Brassica rapa varieties - Fayaz Ali; Kainat; Waqar Khan; Alamgir Khan; Amin Ullah Jan; Muhammad Amin; Carmelo Maria Musarella (Vegetos, 2023)

Nanotechnologies for environmental remediation and their ecotoxicological impacts - Mahnoor Ejaz; Alvina Gul; Munir Ozturk; Ahmed Hafeez; Bengu Turkyilmaz Unal; Sami Ullah Jan; Muhammad Taimur Siddique (Environmental Monitoring and Assessment, 2023)

Recent developments in designing Cu-based electrocatalysts and advanced strategies for electrochemical nitrate reduction to ammonia - Sadeeq Ullah; Shiyong Wang; Changping Li; Amin Ullah Jan; Fei Zhan; Hafiz Muhammad Adeel Sharif; Qingling Liu; Gang Wang (Journal of Environmental Chemical Engineering, 2023)

Bio-fortification of Two Wheat Cultivars with Iron and Zinc Through Their Soil and Foliar Application in Salt-Factored Soil: Growth, Ionic, Physiological, and Biochemical Modifications - Tayyaba Naz; Muhammad Mazhar Iqbal; Shah Fahad; Javaid Akhtar; Muhammad Saqib; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; et al. (Journal of Plant Growth Regulation, 2023)

Barriers to the adoption of social welfare measures in the electricity tariff structure of developing countries: A case of Pakistan - Muhammad Zain Jan; Kafait Ullah; Faisal Abbas; Hassan Abdullah Khalid; Tariq M. Bajwa (Energy Policy, 2023)

Isolation of Endophytic Fungi from Halophytic Plants and their Identification and Screening for Auxin Production and Other Plant Growth Promoting Traits - Muhammad Ikram; Niaz Ali; Gul Jan; Farzana Gul Jan; Rainaz Pervez; Muhammad Romman; Rimsha Zainab; Humaira Yasmin; Naeem Khan (Journal of Plant Growth Regulation, 2023)

Climate, Temporal Abundance of Key Food Sources and Home Ranges of Crested Macaques (Macaca nigra) in Sulawesi, Indonesia: A Longitudinal Phenological Study - Marine Joly; Meldy Tamengge; Jan-Boje Pfeiffer; Megan Price; Muhammad Agil; Antje Engelhardt (International Journal of Primatology, 2023)
Climate change is associated with more frequent extreme weather conditions and an overall increase in temperature around the globe. Its impact on individual ecosystems is not yet well known. Long-term data documenting climate and the temporal abundance of food for primates are scarce. We used long-term phenological data to assess climate variation, fruit abundance and home range sizes of the endemic and Critically Endangered crested macaques ( Macaca nigra ) in Tangkoko forest, Sulawesi, Indonesia. Between January 2012 and July 2020, every month, we monitored 498 individual trees from 41 species and 23 families. We noted each tree’s phenophase and assessed variation in climate (daily temperature and rainfall) and fruit abundance. We also investigated whether individual trees of known key food sources for macaques (New Guinea walnut trees, Dracontomelon spp , two species, N = 10 individual trees; fig trees, Ficus spp , four species, N = 34, and spiked peppers, Piper aduncum , N = 4) showed regular and synchronised fruiting cycles. We used 2877 days of ranging data from four habituated groups to estimate home ranges between January 2012 and July 2020. We created models to evaluate the impact of ecological factors (temperature, rainfall, overall fruit abundance, fig abundance). We found that the temperature increased in Tangkoko forest, and the overall fruit abundance decreased across the study. Top key fruits showed different trends in fruiting. Figs seem to be present year-round, but we did not detect synchrony between individuals of the same species. The macaque home ranges were about 2 km 2 . Monthly temperature was the main predictor of home range size, especially in disturbed forest with previously burnt areas. This information will help to further monitor changes in the macaques’ habitat, and better understand ranging and foraging strategies of a Critically Endangered species and hence contribute to its conservation.

Dyeing of wool fabric with natural dye extracted from Dalbergia Sissoo using natural mordants - Kashif Iqbal; Haseeb Afzal; Muhammad Owais Raza Siddiqui; Uzma Bashir; Khayale Jan; Amir Abbas; Hafiz Affan Abid (Sustainable Chemistry and Pharmacy, 2023)

Islamic corporate sustainability practices index aligned with SDGs towards better financial performance: Evidence from the Malaysian and Indonesian Islamic banking industry - Amin Jan; Haseeb Ur Rahman; Muhammad Zahid; Anas A. Salameh; Parvez Alam Khan; Mamdouh Abdulaziz Saleh Al-Faryan; Roslizawati Binti Che Aziz; H. Elhosiny Ali (Journal of Cleaner Production, 2023)

Detrimental effects of Cd and temperature on rice and functions of microbial community in paddy soils - Raheel Munir; Mehmood Jan; Sajid Muhammad; Muhammad Afzal; Nazia Jan; Muhammad Umair Yasin; Iqbal Munir; Aqib Iqbal; Shuaiqi Yang; Weijun Zhou; Yinbo Gan (Environmental Pollution, 2023)

Finding the sweet spot: a qualitative study exploring patients’ acceptability of chatbots in genetic service delivery - Stephanie Luca; Marc Clausen; Angela Shaw; Whiwon Lee; Suvetha Krishnapillai; Ella Adi-Wauran; Hanna Faghfoury; Gregory Costain; Rebekah Jobling; Melyssa Aronson; Eriskay Liston; Josh Silver; et al. (Human Genetics, 2023)

Alginate magnetic graphene oxide biocomposite synthesis for removal of aromatic amines from aqueous samples - Muhammad Amir Zeb; Jasmin Shah; Muhammad Rasul Jan (Environmental Science and Pollution Research, 2023)

Role of financial development, foreign direct investment inflow, innovation in environmental degradation in Pakistan with dynamic ARDL simulation model - Ali Jan; Zhao Xin-gang; Samreen Fahim Babar; Muhammad Kamran Khan (Environmental Science and Pollution Research, 2023)

Unraveling the mutualistic interaction between endophytic Curvularia lunata CSL1 and tomato to mitigate cadmium (Cd) toxicity via transcriptomic insights - Sajjad Asaf; Rahmatullah Jan; Muhammad Aaqil Khan; Lubna; Abdul Latif Khan; Saleem Asif; Saqib Bilal; Waqar Ahmad; Muhammad Waqas; Kyung-Min Kim; Ahmed AL-Harrasi; In-Jung Lee (Science of The Total Environment, 2023)

Development of methods for the simplification of complex group built causal loop diagrams: A case study of the Rechna doab - Muhammad Asif; Azhar Inam; Jan Adamowski; Muhammad Shoaib; Hisham Tariq; Shakil Ahmad; Mohammad Reza Alizadeh; Aftab Nazeer (Ecological Modelling, 2023)

Corrigendum to “Priorities to inform research on marine plastic pollution in Southeast Asia” [Sci. Total Environ. volume 841 (2022) Article 156704] - Lucy C.M. Omeyer; Emily M. Duncan; Kornrawee Aiemsomboon; Nicola Beaumont; Sujaree Bureekul; Bin Cao; Luis R. Carrasco; Suchana Chavanich; James R. Clark; Muhammad R. Cordova; Fay Couceiro; Simon M. Cragg; et al. (Science of The Total Environment, 2023)

A walk of corporate sustainability towards sustainable development: a bibliometric analysis of literature from 2005 to 2021 - Ahmad Ali Jan; Fong-Woon Lai; Junaid Siddique; Muhammad Zahid; Syed Emad Azhar Ali (Environmental Science and Pollution Research, 2022)

Correction: Fazal et al. Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions. J. Mar. Sci. Eng. 2022, 10, 800 - Abdul Ghaffar Fazal; Muhammad Umar; Faisal Shah; Muhammad Armaghan Faisal Miraj; Hammad Tariq Janjuhah; George Kontakiotis; Abdul Khaliq Jan (Journal of Marine Science and Engineering, 2022)
In the original publication [...]

Capturing spatial variability of factors affecting the water allocation plans—a geo-informatics approach for large irrigation schemes - Muhammad Mohsin Waqas; Muhammad Waseem; Sikandar Ali; Jan W. Hopman; Usman Khalid Awan; Syed Hamid Hussain Shah; Adnan Noor Shah (Environmental Science and Pollution Research, 2022)

Effects of climatic drivers on the genetic divergence of Juglans regia L. across districts Dir and Swat, Khyber Pakhtunkhwa, Pakistan - Mohammad Kamil; Ikramullah Khan; Abdur Rauf; Farooq Jan; Muhammad Irfan (Genetic Resources and Crop Evolution, 2022)

Effects of yeast extract on the production of phenylpropanoid metabolites in callus culture of purple basil (Ocimum Basilicum L. var purpurascens) and their in-vitro evaluation for antioxidant potential - Gouhar Zaman; Umar Farooq; Muhammad Naeem Bajwa; Hasnain Jan; Muzamil Shah; Riaz Ahmad; Anisa Andleeb; Samantha Drouet; Christophe Hano; Bilal Haider Abbasi (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Geology and petrogenesis of gabbro from the Zhob Ophiolite, Balochistan, Pakistan - Abdul Naeem; Muhammad Ishaq Kakar; Rehanul Haq Siddiqui; Andrew C. Kerr; Muhammad Qasim Jan; Muhammad Ayoub Khan (Arabian Journal of Geosciences, 2022)

Geochemical Analysis of Cretaceous Shales from the Hazara Basin, Pakistan: Provenance Signatures and Paleo-Weathering Conditions - Abdul Fazal; Muhammad Umar; Faisal Shah; Muhammad Miraj; Hammad Janjuhah; George Kontakiotis; Abdul Jan (Journal of Marine Science and Engineering, 2022)
The geochemical investigation of shales from the Early to Middle Cretaceous Chichali Formation in the Hazara Basin was conducted to determine the origin, tectonic setting and evolution, paleo-weathering conditions, and paleo-oceanographic reconstruction. The research included a comprehensive field survey, sample collection, and analysis of a variety of main, trace, and rare-earth elements using an X-ray fluorescence spectrometer (XRF). Bivariate plots and ternary diagrams were used to determine the provenance, tectonic setting, and paleo-weathering conditions that existed during the development of the Chichali Formation in the Hazara Basin. The values of Ba/Sc, Ba/Co, Th/Sc, Cr/Th, Cr/Zr, Th/Co, Th/Cr, Sc/Th, bivariate plots of Al2O3 vs. TiO2, TiO2 vs. Zr, TiO2 vs. Ni, Df1–Df2, Zr vs. Nb, and La/Sc vs. Th/Co, and ternary diagram of K2O–Fe2O3–Al2O3 were used to illustrate the passive continental margin setting of Chichali Formation shales. The detailed chemical analysis also provides an understanding of the marine geochemical cycle, which reflects the origin of these sediments. The average K2O/Al2O3 value is less than 0.4, indicating that the shale contains clay minerals. The Chichali Formation’s Chemical Index of Alteration (mean = 71) and Index of Compositional Variation (mean = 1.12) values show a modest degree of chemical weathering in the source locations. From an environmental standpoint, the Chichali Formation is richer in toxic elements such as Ba, Zn, Ni, Cr, and Cu, which may be damaging to agricultural soils and drinking water when present in excess. These metals are incorporated into the formation during the weathering process.

Exploring the potential effect of Achnatherum splendens L.–derived biochar treated with phosphoric acid on bioavailability of cadmium and wheat growth in contaminated soil - Muhammad Irfan; Khadim Dawar; Shah Fahad; Imran Mehmood; Saud Alamri; Manzer H. Siddiqui; Shah Saud; Jabar Zaman Khan Khattak; Shamsher Ali; Shah Hassan; Taufiq Nawaz; Hafiz Mohkum Hammad; et al. (Environmental Science and Pollution Research, 2022)

Endophytic aspergillus oryzae reprograms Abelmoschus esculentus L. to higher growth under salt stress via regulation of physiochemical attributes and antioxidant system - Farzana Gul Jan; Nusrat bibi; Muhammad Hamayun; Yong-Sun Moon; Gul Jan; Maryam Shafique; Sajid Ali (Biologia, 2022)

Diagnostic, prognostic and therapeutic potential of long noncoding RNAs in cancer - Muhammad Babar Khawar; Syeda Eisha Hamid; Tayyba Jan; Muddasir Hassan Abbasi; Muhammad Idnan; Nadeem Sheikh (Molecular Biology Reports, 2022)

Estimation of a trend of meteorological and hydrological drought over Qinhuai River Basin - Mohammad Ilyas Abro; Ehsan Elahi; Ram Chand; Dehua Zhu; Jan Muhammad; Muhammad Rafique Daudpoto; Abdul Majid Soomro; Murad Ali Khaskheli (Theoretical and Applied Climatology, 2022)

Transporters and transcription factors gene families involved in improving nitrogen use efficiency (NUE) and assimilation in rice (Oryza sativa L.) - Tahmina Nazish; Mamoona Arshad; Sami Ullah Jan; Ayesha Javaid; Muhammad Hassaan Khan; Muhammad Afzal Naeem; Muhammad Baber; Mohsin Ali (Transgenic Research, 2022)

Tocopherol as plant protector: an overview of Tocopherol biosynthesis enzymes and their role as antioxidant and signaling molecules - Essa Ali; Sayed Hussain; Nazim Hussain; Kaleem Ullah Kakar; Jawad Munawar Shah; Syed Hassan Raza Zaidi; Masood Jan; Kewei Zhang; Muhammad Ali Khan; Muhammad Imtiaz (Acta Physiologiae Plantarum, 2022)

Impacts of climate change on yield of cereal crops in northern climatic region of Pakistan - Inayatullah Jan; Muhammad Ashfaq; Abbas Ali Chandio (Environmental Science and Pollution Research, 2021)

Do economic openness and electricity consumption matter for environmental deterioration: silver bullet or a stake? - Ali Jan; Zhao Xin-gang; Munir Ahmad; Muhammad Irfan; Shahid Ali (Environmental Science and Pollution Research, 2021)

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

A review of landslides related to the 2005 Kashmir Earthquake: implication and future challenges - Muhammad Basharat; Muhammad Tayyib Riaz; M. Qasim Jan; Chong Xu; Saima Riaz (Natural Hazards, 2021)

Plant growth regulators and EDTA improve phytoremediation potential and antioxidant response of Dysphania ambrosioides (L.) Mosyakin & Clemants in a Cd-spiked soil - Amin Ullah Jan; Fazal Hadi; Abdullah Shah; Allah Ditta; Muhammad Asif Nawaz; Muhammad Tariq (Environmental Science and Pollution Research, 2021)

Influence of rainfall infiltration on the stability of unsaturated coal gangue accumulated slope - Kaleem Ullah Jan Khan; Chang-ming Wang; Muhammad Wasim Jan Khan; Zhu Liang; Shuo Li; Bai-long Li (Journal of Mountain Science, 2021)

Phytosynthesis of poly (ethylene glycol) methacrylate-hybridized gold nanoparticles from C. tuberculata: their structural characterization and potential for in vitro growth in banana - Natasha Anwar; Jan Wahid; Jalal Uddin; Abbas Khan; Mohib Shah; Syed Adil Shah; Fazle Subhan; Mubarak Ali Khan; Kazim Ali; Mamoona Rauf; Muhammad Arif (In Vitro Cellular & Developmental Biology - Plant, 2021)

Biochar and leguminous cover crops as an alternative to summer fallowing for soil organic carbon and nutrient management in the wheat-maize-wheat cropping system under semiarid climate - Muhammad Arif; Ikramullah; Talha Jan; Muhammad Riaz; Kashif Akhtar; Salman Ali; Shahen Shah; Fazal Jalal; Ishaq A. Mian; Khadim Muhammad Dawar; Haiyan Wang (Journal of Soils and Sediments, 2021)

Regional Comparison of Snow Leopard (Panthera uncia) Diet using DNA Metabarcoding - Charlotte E. Hacker; Matthew Jevit; Shafqat Hussain; Ghulam Muhammad; Bariushaa Munkhtsog; Bayaraa Munkhtsog; Yuguang Zhang; Diqiang Li; Yanlin Liu; John D. Farrington; Farida Balbakova; Azat Alamanov; et al. (Biodiversity and Conservation, 2021)

Correction to: Site response studies in Peshawar using the Nakamura technique of HVSR - Sarfraz Khan; Muhammad Waseem; Shoaib Jan (Arabian Journal of Geosciences, 2021)

A review of gas chromatographic techniques for identification of aqueous amine degradation products in carbonated environments - Idris Mohamed Saeed; Shaukat Ali Mazari; Peter Alaba; Brahim Si Ali; Badrul Mohamed Jan; Wan Jeffrey Basirun; Yahaya Muhammad Sani; Sabzoi Nizzamuddin; Nabisab Mujawar Mubarak (Environmental Science and Pollution Research, 2021)

Site response studies in Peshawar using the Nakamura technique of HVSR - Sarfraz Khan; Muhammad Waseem; Shoaib Jan (Arabian Journal of Geosciences, 2021)

Study of the nonlinear character of ionospheric signals possessing critical frequency (foF2) at Pakistan air space - Bulbul Jan; Faisal Ahmed Khan Afridi; Muhammad Ali; Muhammad Ayub Khan Yousufzai (Arabian Journal of Geosciences, 2021)

Modulation of sugar and nitrogen in callus induction media alter PAL pathway, SA and biomass accumulation in rice callus - Rahmatullah Jan; Muhammad Aaqil Khan; Sajjad Asaf; In-Jung Lee; Kyung-Min Kim (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

24-Epibrassinolide Alleviates the Injurious Effects of Cr(VI) Toxicity in Tomato Plants: Insights into Growth, Physio-Biochemical Attributes, Antioxidant Activity and Regulation of Ascorbate–Glutathione and Glyoxalase Cycles - Sumira Jan; Ali Noman; Cengiz Kaya; Muhammad Ashraf; Mohammed Nasser Alyemeni; Parvaiz Ahmad (Journal of Plant Growth Regulation, 2020)

Dechlorane Plus as an emerging environmental pollutant in Asia: a review - Mazhar Iqbal Zafar; Sundas Kali; Mehtabidah Ali; Muhammad Asam Riaz; Tayyaba Naz; Muhammad Mazhar Iqbal; Noshin Masood; Kashif Munawar; Bilal Jan; Sohail Ahmed; Amir Waseem; Muhammad Bilal Khan Niazi (Environmental Science and Pollution Research, 2020)

Assessment of health and ecological risks of heavy metal contamination: a case study of agricultural soils in Thall, Dir-Kohistan - Irshad Ullah; Allah Ditta; Muhammad Imtiaz; Sajid Mehmood; Muhammad Rizwan; Muhammad Shahid Rizwan; Amin Ullah Jan; Iftikhar Ahmad (Environmental Monitoring and Assessment, 2020)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Heavy Metals Level, Health Risk Assessment Associated with Contamination of Black Tea; A Case Study from Khyber Pakhtunkhwa (KPK), Pakistan - Muhammad Idrees; Fazal Akbar Jan; Shah Hussain; Abdul Salam (Biological Trace Element Research, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Eocene carbonate microfacies distribution of the Chorgali Formation, Gali Jagir, Khair-e-Murat Range, Potwar Plateau, Pakistan: approach of reservoir potential using outcrop analogue - Muhammad Awais; Muhammad Hanif; Irfan U. Jan; Muhammad Ishaq; Muhammad Younis Khan (Arabian Journal of Geosciences, 2020)

Characterization of phenolic compounds in two novel lines of Pisum sativum L. along with their in vitro antioxidant potential - Nausheen Nazir; Mohammad Nisar; Sajjad Ahmad; Syed Fazal Wadood; Tour Jan; Muhammad Zahoor; Manzoor Ahmad; Abid Ullah (Environmental Science and Pollution Research, 2020)

Assessment of subsurface lithology, groundwater depth, and quality of UET Lahore, Pakistan, using electrical resistivity method - Zahid Mehmood; Noor Muhammad Khan; Shamsher Sadiq; Saeed-ullah Jan Mandokhail; Syed Zishan Ashiq (Arabian Journal of Geosciences, 2020)

Use of crop growth model to simulate the impact of climate change on yield of various wheat cultivars under different agro-environmental conditions in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Ishfaq Ahmed; Muhammad Ashfaq; Dawood Jan; Shah Fahad; Xiuling Li; Depeng Wang; Muhammad Fahad; Muhammad Fayyaz; Syed Attaullah Shah (Arabian Journal of Geosciences, 2020)

Biological Activities of Artemisinins Beyond Anti-Malarial: a Review - Saeed-ur-Rahman; Muhammad Khalid; Sadaf-Ilyas Kayani; Farooq Jan; Ayaz Ullah; Kexuan Tang (Tropical Plant Biology, 2019)

A Novel Approach to Evaluate, Highlight, and Conserve the Geologically Significant Geoheritage Sites from the Peshawar Basin, Khyber Pakhtunkhwa, Pakistan: Insights into Their Geoscientific, Educational, and Social Importance - Muhammad Yaseen; Mukhtiar Ghani; Muhammad Naveed Anjum; Muhammad Sajid; Irfan Ullah Jan; Mubbashir Mehmood; Emad Ullah; Waqas Muzaffir (Geoheritage, 2019)

DNA barcoding of Haplophyllum gilesii (Hemsel.) C. C. Townsend from the Gilgit-Baltistan Province of Pakistan - Bushra Khan; Habib Ahmad; Jan Alam; Muhammad Shahid Nadeem; Aziz Ud-Din; Inam Ullah; Shafee Ur Rehman; Khushi Muhammad (Brazilian Journal of Botany, 2019)

Modulation in growth, gas exchange, and antioxidant activities of salt-stressed rice (Oryza sativa L.) genotypes by zinc fertilization - Muhammad Jan; Muhammad Anwar-ul-Haq; Adnan Noor Shah; Muhammad Yousaf; Javaid Iqbal; Xiuling Li; Depeng Wang; Shah Fahad (Arabian Journal of Geosciences, 2019)

Temperature Dependence of the Structure and Dynamics of a Dye-Labeled Lipid in a Planar Phospholipid Bilayer: A Computational Study - Muhammad Jan Akhunzada; Luca Sagresti; Andrea Catte; Nicholus Bhattacharjee; Tommaso D’Agostino; Giuseppe Brancato (The Journal of Membrane Biology, 2019)

Knockdown of the chitin-binding protein family gene CaChiIV1 increased sensitivity to Phytophthora capsici and drought stress in pepper plants - Muhammad Ali; Wen-Xian Gai; Abdul Mateen Khattak; Abid Khan; Saeed Ul Haq; Xiao Ma; Ai-Min Wei; Izhar Muhammad; Ibadullah Jan; Zhen-Hui Gong (Molecular Genetics and Genomics, 2019)

Study the stratospheric ozone irregularity over Pakistan atmospheric region in perspectives of wavelet analysis - Bulbul Jan; Muhammad Ayub Khan Yousufzai; Faisal Ahmed Khan Afridi; Faisal Nawaz (Arabian Journal of Geosciences, 2019)

Microfacies and diagenetic studies of the early Eocene Sakesar Limestone, Potwar Plateau, Pakistan: approach of reservoir evaluation using outcrop analogue - Muhammad Ishaq; Irfan U. Jan; Muhammad Hanif; Muhammad Awais (Carbonates and Evaporites, 2019)

Relating petrophysical parameters to petrographic interpretations in carbonates of the Chorgali Formation, Potwar Plateau, Pakistan - Muhammad Awais; Muhammad Hanif; Muhammad Younis Khan; Irfan U. Jan; Muhammad Ishaq (Carbonates and Evaporites, 2019)

Novel antimicrobial and antioxidative activity by endophytic Penicillium roqueforti and Trichoderma reesei isolated from Solanum surattense - Muhammad Ikram; Niaz Ali; Gul Jan; Muhammad Hamayun; Farzana Gul Jan; Amjad Iqbal (Acta Physiologiae Plantarum, 2019)

Oxindole-based chalcones: synthesis and their activity against glycation of proteins - Ayesha Khan; Ajmal Khan; Umar Farooq; Muhammad Taha; Syed Adnan Ali Shah; Sobia Ahsan Halim; Arfa Akram; Mohammed Ziauddin Khan; Abdul Khaliq Jan; Ahmed Al-Harrasi (Medicinal Chemistry Research, 2019)

Performance of Aeluropus lagopoides (mangrove grass) ecotypes, a potential turfgrass, under high saline conditions - Muhammad Zamin; Abdul Mateen Khattak; Abdul Mohsin Salim; Kenneth B. Marcum; Muhammad Shakur; Shahen Shah; Ibadullah Jan; Shah Fahad (Environmental Science and Pollution Research, 2019)

Sub-lethal effects of lufenuron exposure on spotted bollworm Earias vittella (Fab): key biological traits and detoxification enzymes activity - Muhammad Hafeez; Saad Jan; Muhammad Nawaz; Ehsan Ali; Bahar Ali; Muhammad Qasim; G. Mandela Fernández-Grandon; Muhammad Shahid; Mo Wang (Environmental Science and Pollution Research, 2019)

Roles of potential plant hormones and transcription factors in controlling leaf senescence and drought tolerance - Sumira Jan; Nazia Abbas; Muhammad Ashraf; Parvaiz Ahmad (Protoplasma, 2019)

Assessing the socio-economic impact of climate change on wheat production in Khyber Pakhtunkhwa, Pakistan - Farhana Gul; Dawood Jan; Muhammad Ashfaq (Environmental Science and Pollution Research, 2019)

Hemp (Marijuana) reverted Copper-induced toxic effects on the essential fatty acid profile of Labeo rohita and Cirrhinus mrigala - Azam Jan Afridi; Amina Zuberi; Ali Muhammad Yousafzai; Maria; Muhammad Kamran; Sana Ullah (Molecular Biology Reports, 2019)

Halo-tolerant rhizospheric Arthrobacter woluwensis AK1 mitigates salt stress and induces physio-hormonal changes and expression of GmST1 and GmLAX3 in soybean - Muhammad Aaqil Khan; Ihsan Ullah; Muhammad Waqas; Muhammad Hamayun; Abdul Latif Khan; Sajjad Asaf; Sang-Mo Kang; Kyung-Min Kim; Rahmatullah Jan; In-Jung Lee (Symbiosis, 2019)

Multiple Aneurysms AnaTomy CHallenge 2018 (MATCH): Phase I: Segmentation - Philipp Berg; Samuel Voß; Sylvia Saalfeld; Gábor Janiga; Aslak W. Bergersen; Kristian Valen-Sendstad; Jan Bruening; Leonid Goubergrits; Andreas Spuler; Nicole M. Cancelliere; David A. Steinman; Vitor M. Pereira; et al. (Cardiovascular Engineering and Technology, 2018)

A novel Salvialactomine from the callus culture of Salvia santolinifolia Boiss - Tour Jan; Raiha Qadri; Beena Naqvi; Achyut Adhikari; Said Nadeem; Akhtar Muhammad (Natural Product Research, 2018)

Phytochemical composition, biological potential and enzyme inhibition activity of Scandix pecten-veneris L. - Abdul Wahab; Syed Aleem Jan; Abdur Rauf; Zia ur Rehman; Zahid Khan; Aftab Ahmed; Fatima Syed; Sher Zaman Safi; Hamayun Khan; Muhammad Imran (Journal of Zhejiang University-SCIENCE B, 2018)

P21Waf1/Cip1 depletion promotes dexamethasone-induced apoptosis in osteoblastic MC3T3-E1 cells by inhibiting the Nrf2/HO-1 pathway - Dandan Han; Jian Gao; Xiaolong Gu; Jan Georg Hengstler; Limei Zhang; Muhammad Shahid; Tariq Ali; Bo Han (Archives of Toxicology, 2018)

Ellis–van Creveld syndrome and profound deafness resulted by sequence variants in the EVC / EVC2 and TMC1 genes - Muhammad Umair; Heide Seidel; Ishtiaq Ahmed; Asmat Ullah; Tobias B. Haack; Bader Alhaddad; Abid Jan; Afzal Rafique; Tim M. Strom; Farooq Ahmad; Thomas Meitinger; Wasim Ahmad (Journal of Genetics, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Felsic dykes in the Neoproterozoic Nagar Parkar Igneous Complex, SE Sindh, Pakistan: geochemistry and tectonic settings - Tahseenullah Khan; Mamoru Murata; M. Qasim Jan; Hafiz Ur Rehman; Muhammad Zafar; Hiroaki Ozawa; Anwar Qadir; Saqib Mehmood (Arabian Journal of Geosciences, 2017)

Are Karakoram temperatures out of phase compared to hemispheric trends? - Fayaz Asad; Haifeng Zhu; Hui Zhang; Eryuan Liang; Sher Muhammad; Suhaib Bin Farhan; Iqtidar Hussain; Muhammad Atif Wazir; Moinuddin Ahmed; Jan Esper (Climate Dynamics, 2017)

Production of α-1,4-glucosidase from Bacillus licheniformis KIBGE-IB4 by utilizing sweet potato peel - Muhammad Asif Nawaz; Zainab Bibi; Asad Karim; Haneef Ur Rehman; Muhsin Jamal; Tour Jan; Afsheen Aman; Shah Ali Ul Qader (Environmental Science and Pollution Research, 2017)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Osmoregulation and antioxidant production in maize under combined cadmium and arsenic stress - Shakeel Ahmad Anjum; Mohsin Tanveer; Saddam Hussain; Babar Shahzad; Umair Ashraf; Shah Fahad; Waseem Hassan; Saad Jan; Imran Khan; Muhammad Farrukh Saleem; Ali Ahsan Bajwa; Longchang Wang; et al. (Environmental Science and Pollution Research, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Climate‐driven changes to the spatio‐temporal distribution of the parasitic nematode, Haemonchus contortus, in sheep in Europe - Hannah Rose; Cyril Caminade; Muhammad Bashir Bolajoko; Paul Phelan; Jan van Dijk; Matthew Baylis; Diana Williams; Eric R. Morgan (Global Change Biology, 2016)
Recent climate change has resulted in changes to the phenology and distribution of invertebrates worldwide. Where invertebrates are associated with disease, climate variability and changes in climate may also affect the spatio‐temporal dynamics of disease. Due to its significant impact on sheep production and welfare, the recent increase in diagnoses of ovine haemonchosis caused by the nematode Haemonchus contortus in some temperate regions is particularly concerning. This study is the first to evaluate the impact of climate change on H. contortus at a continental scale. A model of the basic reproductive quotient of macroparasites, Q 0 , adapted to H. contortus and extended to incorporate environmental stochasticity and parasite behaviour, was used to simulate Pan‐European spatio‐temporal changes in H. contortus infection pressure under scenarios of climate change. Baseline Q 0 simulations, using historic climate observations, reflected the current distribution of H. contortus in Europe. In northern Europe, the distribution of H. contortus is currently limited by temperatures falling below the development threshold during the winter months and within‐host arrested development is necessary for population persistence over winter. In southern Europe, H. contortus infection pressure is limited during the summer months by increased temperature and decreased moisture. Compared with this baseline, Q 0 simulations driven by a climate model ensemble predicted an increase in H. contortus infection pressure by the 2080s. In northern Europe, a temporal range expansion was predicted as the mean period of transmission increased by 2–3 months. A bimodal seasonal pattern of infection pressure, similar to that currently observed in southern Europe, emerges in northern Europe due to increasing summer temperatures and decreasing moisture. The predicted patterns of change could alter the epidemiology of H. contortus in Europe, affect the future sustainability of contemporary control strategies, and potentially drive local adaptation to climate change in parasite populations.

Geochemistry and petrogenesis of Oligocene volcaniclastic rocks from the Chagai arc: implications for the emplacement of porphyry copper deposits - Rehanul Haq Siddiqui; Muhammad Asif Khan; Muhammad Qasim Jan; Mohammad Ishaq Kakar; Andrew C. Kerr (Arabian Journal of Geosciences, 2015)

Baseline susceptibility and resistance stability of Earias vittella fabricius (Lepidoptera: Noctuidae) to cypermethrin, deltamethrin and spinosad - Muhammad Tahir Jan; Naeem Abbas; Sarfraz Ali Shad; Muhammad Rafiq; Mushtaq Ahmad Saleem (Phytoparasitica, 2015)

The Early Cambrian Khewra Sandstone, Salt Range, Pakistan: endorsing southern Indian provenance - Mubashir Jehangiri; Muhammad Hanif; Muhammad Arif; Irfan U. Jan; Sajjad Ahmad (Arabian Journal of Geosciences, 2015)

Using larger benthic foraminifera for the paleogeographic reconstruction of Neo-Tethys during Paleogene - Sajjad Ahmad; Wahid Jalal; Fahad Ali; Muhammad Hanif; Zaheen Ullah; Suleman Khan; Asghar Ali; Irfan U. Jan; Khaista Rehman (Arabian Journal of Geosciences, 2015)

Potential role of phytohormones and plant growth-promoting rhizobacteria in abiotic stresses: consequences for changing environment - Shah Fahad; Saddam Hussain; Asghari Bano; Shah Saud; Shah Hassan; Darakh Shan; Faheem Ahmed Khan; Fahad Khan; Yutiao Chen; Chao Wu; Muhammad Adnan Tabassum; Ma Xiao Chun; et al. (Environmental Science and Pollution Research, 2015)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)

A Validated Spectrofluorimetric Method for the Determination of Citalopram in Bulk and Pharmaceutical Preparations Based on the Measurement of the Silver Nanoparticles-Enhanced Fluorescence of Citalopram/Terbium Complexes - Muhammad Naeem Khan; Jasmin Shah; Muhammad Rasul Jan; Sang Hak Lee (Journal of Fluorescence, 2013)

Genetic diversity in human malarial parasites of Khyber Agency Pakistan - Lubna Khatoon; Muhammad Jan; Inam Khan; Farhat Ullah; Salman Malik (Acta Parasitologica, 2013)
Malaria is wide spread in poor world and its burden has been assessed by the enumeration of malarial parasites in blood of patients. This study was designed to find a relationship between social structure, and spread of malaria in Khyber agency. The average parasite density was 2050 parasite/μl in Khyber Agency. Due to economic and social setup most of the people have habit of sleeping in open air thus playing role in high malaria prevalence and Plasmodium vivax remains the prevalent species. Genetic study performed on 110 Blood samples showed less genetic diversity for both Plasmodium vivax and Plasmodium falciparum. Eight alleles were distinguished both for Pvmsp 3α and Pvmsp 3β in total of 20 and 39 amplified samples of P. vivax respectively. Out of 17 samples amplified for P. falciparum 11 showed genotype K1 and 10 for MAD at Pfmsp-1 while 14 alleles were identified for 3D7/1C and two for FC27 of corresponding families of Pfmsp-2 gene. This shows that Plasmodium parasites are not genetically diverse in Khyber agency.

Rs11892031[A] on chromosome 2q37 in an intronic region of the UGT1A locus is associated with urinary bladder cancer risk - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Root colonization and growth promotion of sunflower (Helianthus annuus L.) by phosphate solubilizing Enterobacter sp. Fs-11 - Muhammad Shahid; Sohail Hameed; Asma Imran; Saira Ali; Jan Dirk van Elsas (World Journal of Microbiology and Biotechnology, 2012)

An Alu repeat-mediated genomic GCNT2 deletion underlies congenital cataracts and adult i blood group - Guntram Borck; Naseebullah Kakar; Jochen Hoch; Katrin Friedrich; Jan Freudenberg; Gudrun Nürnberg; Rüstem Yilmaz; Shakeela Daud; Dost Muhammad Baloch; Peter Nürnberg; Johannes Oldenburg; Jamil Ahmad; et al. (Human Genetics, 2012)

Urinary bladder cancer risk in relation to a single nucleotide polymorphism (rs2854744) in the insulin-like growth factor-binding protein-3 (IGFBP3) gene - Silvia Selinski; Marie-Louise Lehmann; Meinolf Blaszkewicz; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truß; Holger Gerullis; Thomas Otto; Dimitri Barski; Günter Niegisch; et al. (Archives of Toxicology, 2012)

Food habits of the snow leopard Panthera uncia (Schreber, 1775) in Baltistan, Northern Pakistan - Muhammad Bilal Anwar; Rodney Jackson; Muhammad Sajid Nadeem; Jan E. Janečka; Shafqat Hussain; Mirza Azhar Beg; Ghulam Muhammad; Mazhar Qayyum (European Journal of Wildlife Research, 2011)

Rs710521[A] on chromosome 3q28 close to TP63 is associated with increased urinary bladder cancer risk - Marie-Louise Lehmann; Silvia Selinski; Meinolf Blaszkewicz; Michael Orlich; Daniel Ovsiannikov; Oliver Moormann; Christoph Guballa; Alexander Kress; Michael C. Truss; Holger Gerullis; Thomas Otto; Dimitri Barski; et al. (Archives of Toxicology, 2010)

Heavy Metal Residues in the Milk of Cattle and Goats During Winter Season - Ijaz Javed; Ibadullah Jan; Faqir Muhammad; Zia-ur-Rahman; M. Zargham Khan; Bilal Aslam; Javed Iqbal Sultan (Bulletin of Environmental Contamination and Toxicology, 2009)